2019
DOI: 10.1097/moh.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

MICROtransplant to refractory acute myeloid leukemia in Egyptian population

Abstract: Purpose of review The purpose of this review is to outline Egyptian experience of nonengraftment haploidentical cellular therapy [microtransplantation (MST)] for patients with refractory acute myeloid leukemia. Recent findings The use of granulocyte colony-stimulating factor primed halo-identical MST appears to be a biologically active therapy in patients with refractory acute myeloid leukemia (AML), especially in patients received less than four previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are 13 published reports of studies using a microtransplantation approach for persons with AML only (Table). A randomized clinical trial of elderly individuals (>65 years of age) with AML compared chemotherapy with (n = 28) or without (n = 30) microtransplantation . Participants receiving a microtransplant had a higher rate of histologic complete remission (80% [95% CI, 65%-95%] vs 43% [95% CI, 23%-63%]; P = .006), 2-year leukemia-free survival (39% [95% CI, 20%-58%] vs 10% [95% CI, 0%-20%]; P = .01) and 2-year survival (39% [95% CI, 21%-57%] vs 10% [95% CI, 0%-22%]; P = .006).…”
Section: Resultsmentioning
confidence: 99%
“…There are 13 published reports of studies using a microtransplantation approach for persons with AML only (Table). A randomized clinical trial of elderly individuals (>65 years of age) with AML compared chemotherapy with (n = 28) or without (n = 30) microtransplantation . Participants receiving a microtransplant had a higher rate of histologic complete remission (80% [95% CI, 65%-95%] vs 43% [95% CI, 23%-63%]; P = .006), 2-year leukemia-free survival (39% [95% CI, 20%-58%] vs 10% [95% CI, 0%-20%]; P = .01) and 2-year survival (39% [95% CI, 21%-57%] vs 10% [95% CI, 0%-22%]; P = .006).…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter clinical study found a high CR rate (74.6%) in AML patients aged 60 to 85 years after microtransplantation, with 1.1% underwent GVHD ( 10 ). And 7 patients of the mean age 31.3 years old got microtransplantaion without significant GVHD ( 11 ). However, safety and effectiveness of microtransplantation are still under dispute and need to be evaluated in large randomized clinical trials ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microtransplantation, HLA-mismatched granulocyte colony-stimulating factor-mobilized donor peripheral blood stem-cell infusion, had demonstrated improved survival and limited GVHD in both elderly and young AML patients following chemotherapy ( [10] , [11] , [12] , [13] ). It provides an alternative solution for patients without HLA-matched donors by overcoming the limitations of HLA restriction.…”
Section: Introductionmentioning
confidence: 99%